2009
DOI: 10.1016/j.diagmicrobio.2009.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of multiresistant variants of the community-acquired methicillin-resistant Staphylococcus aureus lineage ST1-SCCmecIV in 2 hospitals in Rio de Janeiro, Brazil

Abstract: Usually, community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) is susceptible to a variety of non-beta-lactam drugs. These isolates commonly display SCCmecIV and are associated with community-acquired infections. More recently, CA-MRSA has been isolated from health-care-associated diseases. We characterized MRSA isolates from 2 hospitals in Rio de Janeiro area to assess the entry of new lineages. The isolates were primary genotyped using a combination of molecular typing methods including SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 35 publications
2
43
0
5
Order By: Relevance
“…Epidemiological data are still limited in Africa; however, the predominance of CC8 (ST239 and ST612), CC5 (ST5) and CC30 (ST36) was suggested ( Moodley et al 2010 , Breurec et al 2011 , Van Rensburg et al 2011 , Shittu et al 2012 ). In Latin America, isolates belonging to CC5 (ST5) and CC8 (ST239) are frequently reported in hospitals ( Silva-Carvalho et al 2009 , Rodríguez-Noriega et al 2010 , Caiaffa-Filho et al 2013) and, in Brazil, the nosocomial lineages ST5-SCC mec I (Cordobes/Chilean clone), ST5-SCC mec IV (USA800; paediatric clone) and ST5-SCC mec II (USA100; clone NY/Japan) are prevailing in some hospitals (de Miranda et al 2007 , Silva-Carvalho et al 2009 , Becker et al 2012 , Caiaffa-Filho et al 2013). Moreover, MRSA isolates of the lineage ST239-SCC mec III [Brazilian epidemic clone (BEC)] are still predominantly detected in various regions of this country ( Silva-Carvalho et al 2009 , Caboclo et al 2013 , Rodrigues et al 2013 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological data are still limited in Africa; however, the predominance of CC8 (ST239 and ST612), CC5 (ST5) and CC30 (ST36) was suggested ( Moodley et al 2010 , Breurec et al 2011 , Van Rensburg et al 2011 , Shittu et al 2012 ). In Latin America, isolates belonging to CC5 (ST5) and CC8 (ST239) are frequently reported in hospitals ( Silva-Carvalho et al 2009 , Rodríguez-Noriega et al 2010 , Caiaffa-Filho et al 2013) and, in Brazil, the nosocomial lineages ST5-SCC mec I (Cordobes/Chilean clone), ST5-SCC mec IV (USA800; paediatric clone) and ST5-SCC mec II (USA100; clone NY/Japan) are prevailing in some hospitals (de Miranda et al 2007 , Silva-Carvalho et al 2009 , Becker et al 2012 , Caiaffa-Filho et al 2013). Moreover, MRSA isolates of the lineage ST239-SCC mec III [Brazilian epidemic clone (BEC)] are still predominantly detected in various regions of this country ( Silva-Carvalho et al 2009 , Caboclo et al 2013 , Rodrigues et al 2013 ).…”
mentioning
confidence: 99%
“…Shortly after, a rare and severe case of pyomyositis, that was associated with compartment syndrome, was also described in Rio de Janeiro city, Brazil, in a previously healthy child (de Araújo et al 2010 ). Unfortunately, few studies regarding the prevalence of CA-MRSA have been reported in Brazil; therefore, little is known about the lineages involved and their prevalence in humans and animals ( Ribeiro et al 2007 , Silva-Carvalho et al 2009 , de Araújo et al 2010 , Ferreira et al 2012 , Camargo et al 2013 ). Recent data from Argentina have reported the predominance of ST30-SCC mec IV in community-acquired invasive infections ( Fernandez et al 2013 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, most S. aureus isolates carrying the pvl genes are related to ST30 (12). To our knowledge, this is the first report of the presence of an ST25-related MSSA strain carrying PVL genes worldwide.…”
mentioning
confidence: 82%
“…No Brasil, já foram notificados casos de "superbactérias", intituladas dessa forma por serem organismos multirresistentes aos antibióticos existentes e, como consequência, a Agência Nacional de Vigilância Sanitária (ANVISA) determinou a publicação de medidas regulatórias, publicadas em outubro de 2010, com o propósito de reduzir a exposição da população aos antibióticos e, com isso, combater a resistência bacteriana (SILVA-CARVALHO et al, 2009). Essa determinação inicialmente provocou uma redução significativa nas vendas de antibióticos no país, no entanto em 2012 os números voltaram a crescer atingindo valores apresentados nas medidas regulatórias, mantendo assim o elevado nível de comercialização desses medicamentos (SINDUSFARMA, 2012).Assim, as infecções causadas por micro-organismos mutantes resistentes, tendem a comprometer o tratamento de pacientes fazendo com que estes tenham que prolongar o mesmo, elevando os custos e aumentando o risco de morte além de contágio de outras pessoas com essas "superbactérias".…”
Section: Introductionunclassified